The Impact of Uncontrolled Type 2 Diabetes Mellitus on Chronic Rhinosinusitis Severity and Treatment Outcomes: A Prospective Cohort Study in Bandung, Indonesia - Zainal Abidin Hasan; Aisyah Andina Rasyid; Hasrita Soleiman; Alexander Mulya; Pham Uyen; Maria Rodriguez (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Chronic rhinosinusitis (CRS) is a prevalent inflammatory condition, and type 2 diabetes mellitus (T2DM) is a known comorbidity that can exacerbate inflammatory processes. This study aimed to investigate the impact of uncontrolled T2DM on CRS severity and treatment outcomes in a cohort of patients in Bandung, Indonesia. Methods: A prospective cohort study was conducted at a private hospital in Bandung, Indonesia, from January 2020 to December 2022. Adult patients diagnosed with CRS (with or without nasal polyps) were enrolled and categorized into two groups: controlled T2DM (HbA1c ≤ 7%) and uncontrolled T2DM (HbA1c > 7%). CRS severity was assessed using the Sino-Nasal Outcome Test-22 (SNOT-22) and Lund-Mackay CT scoring. Treatment outcomes were evaluated at 3, 6, and 12 months post-initial treatment (medical and/or surgical) based on SNOT-22 scores, endoscopic findings, and the need for revision surgery. Results: A total of 240 patients were included (120 with controlled T2DM, 120 with uncontrolled T2DM). At baseline, the uncontrolled T2DM group had significantly higher mean SNOT-22 scores (58.5 ± 12.3 vs. 45.2 ± 10.1, p < 0.001) and Lund-Mackay CT scores (11.8 ± 3.5 vs. 8.2 ± 2.8, p < 0.001) compared to the controlled T2DM group. At 12 months, the uncontrolled T2DM group showed significantly less improvement in SNOT-22 scores (mean change: -15.4 ± 8.7 vs. -28.3 ± 9.2, p < 0.001) and a higher rate of revision surgery (18.3% vs. 5.8%, p = 0.002). Multivariate analysis revealed that uncontrolled T2DM (HbA1c > 7%) was an independent predictor of poorer treatment outcomes (OR: 3.45, 95% CI: 1.98-6.01, p < 0.001). Conclusion: Uncontrolled T2DM is associated with increased CRS severity and significantly poorer treatment outcomes in patients in Bandung, Indonesia. Effective glycemic control should be a crucial component of CRS management in patients with T2DM.